(untitled) (Revista Internacional de Folkcomunicação, 2024)
I propose, in this article, the analysis of texts from the production of the popular poet Antonio Juraci Siqueira, the Boto. I justify this choice because he is a disseminator of Amazonian culture, since in his productions there are linguistic, cultural, legendary and popular echoes of the Pará Amazon; thus, I seek to give the author’s texts a place of voice, a space in which there can be an academic legitimacy for these values of popular production, arising from a tradition, since in each region of Brazil there are writers, in verse and prose, inserted in the among the people, in whose compositions lie legends, myths and real facts that arrive in simple language, full of meaning. Through this language, stories are constructed based on a specific conception of the world and on popular tradition, and these are the characteristics addressed in this study. KEY-WORDS Popular narratives; Amazonian culture; Popular tradition.